Determinants of Services Sector Growth in Pakistan - Ajmair, Muhammad; Gilal, MuhammadAkram; Hussain, Khadim (European Scientific Journal, ESJ, 2016)
Services sector is one of the important sectors of the economy. It contributes more than half of the GDP and has substantial share in country’s exports and employment. In this study we evaluated the factors affecting services sector output growth using annual data from 1975 to 2014 and ARDL method of estimation. Pakistan’s break up in two wings in December, 1971 and availability of data on most of the variables after 1975 determined the choice of sample period. Results show foreign trade, government expenditures, market size and population growth are the relevant determinants of services sector output growth in long run. In short run, services sector growth is affected by foreign trade and personal remittances. Diagnostic tests show absence of serial correlation and parameter stability. Based on estimated results, it is recommended that relevant authorities should implement policies that increase services sector output growth if they intend to augment overall economic growth of the country.